Reducing the Gender Digital Divide Amongst Immigrant Entrepreneurs - Nick Drydakis (Institute of Labor Economics (IZA), 2024)
Information and communication technology (ICT) can boost existing socio-economic inequalities if the former is socially exclusive. Longstanding barriers prevent minoritized populations from accessing ICT, thus leading to a vicious circle between digital divide and poor development. The digital divide can be most important when assessing United Nations (UN) sustainable development goals No. 4 (lifelong learning opportunities), No. 5 (empowerment), No. 8 (growth), and No. 10 (reduced inequalities). The current study presents the outcomes of a business apps training intervention, targeting immigrant entrepreneurs running small firms in Greece, Cyprus and the UK. Multifaceted gender digital divides were unravelled, and training was found to improve entrepreneurs' internet/digital skills and firms' digital competencies, whilst also boosting empowerment and reducing gender digital disparities. Given the positive contribution of immigrant firms to countries' growth, ways to facilitate sustainable performances through digital skills training merit consideration. Further, improving immigrant female entrepreneurs' digital skills requires intersectional approaches that address a vector of socio-economic and cultural barriers, ensuring that ICT-driven sustainable development is much more inclusive.
Keywords: O3; M2; 330; immigrants; digital divide; information and communication technology; business apps training; empowerment; digital competencies